Effect of the choice of drawbead type on the spring back: comparative study between two types of drawbead - Bouzaffour, Mohamed; Fartouh, Yassine; Nassraoui, Mohammed (Zielona Góra: Uniwersytet Zielonogórski)
The stamping process is mainly used in the automotive industry to manufacture parts. However, there is a major problem with the geometrical variations of the part which lead to assembly difficulties, this problem is known as the spring back, that is to say the propensity of the sheet to recover its original shape after being deformed, this results in a geometric variation of the part which affects the final assembly.
Keywords: step bead; spring back; stamping; drawbead; sheet metal